JAG consensus statements for training and certification in oesophagogastroduodenoscopy. Issue 3 (24th January 2022) - Siau, Keith; Beales, Ian L P; Haycock, Adam; Alzoubaidi, Durayd; Follows, Rachael; Haidry, Rehan; Mannath, Jayan; McConnell, Susan; Murugananthan, Aravinth; Ravindran, Srivathsan; Riley, Stuart A; Williams, R N; et al.
Abstract : Introduction: Training and quality assurance in oesophagogastroduodenoscopy (OGD) is important to ensure competent practice. A national evidence-based review was undertaken to update and develop standards and recommendations for OGD training and certification. Methods: Under the oversight of the Joint Advisory Group (JAG), a modified Delphi process was conducted with stakeholder representation from British Society of Gastroenterology, Association of Upper Gastrointestinal Surgeons, trainees and trainers. Recommendations on OGD training and certification were formulated following literature review and appraised using Grading of Recommendations Assessment, Development and Evaluation. These were subjected to electronic voting to achieve consensus. Accepted statements were incorporated into the updated certification pathway. Results: In total, 32 recommendation statements were generated for the following domains: definition of competence (4 statements), acquisition of competence (12 statements), assessment of competence (10 statements) and post-certification support (6 statements). The consensus process led to following certification criteria: (1) performing ≥250 hands-on procedures; (2) attending a JAG-accredited basic skills course; (3) attainment of relevant minimal performance standards defined by British Society of Gastroenterology/Association of Upper Gastrointestinal Surgeons of Great Britain and Ireland, (4) achieving physically unassisted D2 intubation and J-manoeuvre in ≥95% of recent procedures, (5) satisfactory performance in formative and summative direct observation of procedural skills assessments. Conclusion: The JAG standards for diagnostic OGD have been updated following evidence-based consensus. These standards are intended to support training, improve competency assessment to uphold standards of practice and provide support to the newly-independent practitioner.